An Evaluation of the English Textbook Grow with English for Fourth-grade Elementary School Students - Ratini Rahmawati; Evi Karlina Ambarwati (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Textbooks are the major instructional resource that has a crucial role in the teaching and learning process. To obtain an appropriate textbook, a teacher must evaluate or analyze it before applying it in the classroom. A textbook is expected to cover student needs, support national education goals and implement curriculum values. However, in reality, many textbooks still need to meet the criteria of a good textbook based on previous studies, and most of the research is done on high school English textbooks. Therefore, this research examines the suitability and quality of the four-grade primary school English textbook (Grow with English for grade four). This study used descriptive qualitative research and adapted adopted the BSNP (Badan Standar Nasional Pendidikan) framework and theory of Developing Criteria for Textbook Evaluation by David Williams (1983) in analyzing the textbook. The findings show that this textbook follows the 2013 ELT (English Language Teaching) curriculum of Indonesian Education goals and Indonesia's National Education goals. Furthermore, this textbook meets William's (1983) criteria, such as being designed with meaningful drills and learning activities, connecting to the student's age, interests, culture, and environment, having guidance for teachers and students, and graphically having good quality. Then, for further research, observing and analyzing other EFL (English as a Foreign Language) textbooks is recommended to see if they meet the criteria for a good textbook.